Malaysia today : towards the new millennium - ASEAN Academic Press (London : ASEAN Academic Press, 1997)
For the Asian Strategy & Leadership Institute
Keywords: Industrialization -- Malaysia; Infrastructure (Economics) -- Malaysia; Malaysia -- Economic conditions; Malaysia -- Foreign relations